Enhancing Member Participation through Socialization: A Case Study of the Merah Putih Cooperative - Nur Aini; Hendra Riofita (INCARE, International Journal of Educational Resources, 2026)
This istudy iaims ito ianalyze ithe irole iof isocialization iin iencouraging imember iparticipation iin ithe iRed iand iWhite iCooperative. iThe iresearch imethod iused iis ia iqualitative iapproach iwith ia iliterature ireview idesign, iexamining ivarious iscientific isources isuch ias ijournals, iarticles, iand iprevious istudies irelevant ito ithe iresearch itopic. iThe iresults iof ithe istudy iindicate ithat isocialization iplays ia ivery iimportant irole iin iincreasing icooperative imember iparticipation. iSocialization ifunctions ias ia imeans iof idelivering iinformation, ieducation, iand ibuilding imembers’ iawareness iregarding ithe iobjectives, ibenefits, iand ioperational imechanisms iof ithe icooperative. iThrough ieffective iand icontinuous isocialization, imembers igain ia ibetter iunderstanding iof itheir irights iand iobligations, iwhich iencourages ithem ito iactively iparticipate iin icooperative iactivities, isuch ias iattending imember imeetings, icontributing ito icapital, iand iutilizing icooperative iservices. iIn iaddition, isocialization ialso ienhances imembers’ imotivation iand isense iof ibelonging itoward ithe icooperative. iHowever, iits iimplementation istill ifaces iseveral ichallenges, iincluding ilow imember iinterest, ilimited iresources, iand idiverse imember ibackgrounds. iTherefore, iinnovative iand iadaptive isocialization istrategies iare irequired, isuch ias ithe iuse iof idigital imedia iand iinterpersonal iapproaches. iThis istudy iconcludes ithat isocialization iis ia ikey ifactor iin iincreasing imember iparticipation, iwhich iultimately icontributes ito ithe isuccess iof ithe icooperative.